2014
DOI: 10.1038/srep05349
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses to thermal variation between fitness metrics

Abstract: Temperature is a major factor affecting population abundance and individual performance. Net reproductive rate (R0) and intrinsic rate of increase (r) differ in their response to different temperature regimes, and much of the difference is mediated by generation time (Tg). Here, we evaluate the effects of thermal mean and variability on R0, r and Tg, at four population densities in Drosophila melanogaster. The results show that R0, r and Tg present differential responses to thermal variation. Although temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…For example, recent experimental evidence indicated that under some conditions, changes in EN and generation time can constrain (cancel each other out) changes in r , resulting in a similar daily rate of increase under different scenarios of variability (Clavijo‐Baquet et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent experimental evidence indicated that under some conditions, changes in EN and generation time can constrain (cancel each other out) changes in r , resulting in a similar daily rate of increase under different scenarios of variability (Clavijo‐Baquet et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; Clavijo‐Baquet et al. ). The development of a widely accepted theoretical basis should relate physiology to population processes and address the role of temperature means and variability at higher ecological levels and their potentially nonadditive interaction shaping performance.…”
Section: Toward a Unifying Experimental Approachmentioning
confidence: 99%
“…More recently, Clavijo‐Baquet et al . () found similar results for the effects of thermal mean and variability on R 0 , r and the generation length T g , of D. melanogaster , with no effects of temperature variation on r despite strong effects on R 0 and T g . Thus, considering that r ≈ ln ( R 0 )/ T g , thermal effects on R 0 and T g cancel each other.…”
Section: Physiology Individual Performance and Fitnessmentioning
confidence: 99%